Coupling coordination degree and influencing factors of forestry modernization and high quality economic development: an empirical study from provincial panel in China - Zhou, Chao; Wan, Shenwei; Liu, Jia; Ma, Ye; Zheng, Hongling; Chen, Song (Frontiers in Public Health, 2024)
Forestry modernization (FM) and High quality economic development (HED) are two major goals that must be achieved in the process of economic development from low to high, and they are closely related to each other in their respective internal development mechanisms. Based on the analysis of the coupling coordination mechanism between FM and HED, this paper empirically studies the coupling coordination degree and influencing factors of "forestry modernization and high quality economic development" ("FM-HED") using panel data from 30 provinces and cities in China (except Xizang, Hong Kong, Macao and Taiwan) from 2012 to 2020. First, the entropy method and the coupling coordination degree model were used to analyze the temporal changes and spatial differentiation of the coupling coordination between FM and HED. Second, the Tobit model is used to find out the factors affecting the coupling coordination degree of FM and HED. The following conclusions are obtained:(1) The coupling coordination degree of the "FM-HED" system increased rapidly in the early stage and slowly increased in the later period from 2012 to 2020. (2) The level of FM and HED in China in 2012 was obviously unbalanced and insufficient, the coupling coordination degree between the eastern and western provinces and cities was improved in 2015, and the imbalance between regions was alleviated, and the difference in the coupling coordination degree between coastal provinces and cities and inland provinces and cities in 2020 was prominent, and the coastal areas were significantly better than the inland areas. (3) From the national level, the intensity of R&D investment and the burden of the elderly population have a significant effect on the coupling and coordinated development of the two systems. From the perspective of the four regions, the role of R&D investment intensity is reflected in Northeast China and Central China. The role of labor force level is reflected in East China, Northeast China and Northwest China. The role of industrial agglomeration is reflected in Northeast China. The role of the burden of the elderly population is reflected in Northeast China. The role of government intervention is reflected in East China and Northeast China.